Stearic acid blunts growth-factor signaling via oleoylation of GNAI proteins - Nůsková, Hana; Serebryakova, Marina V.; Ferrer-Caelles, Anna; Sachsenheimer, Timo; Lüchtenborg, Christian; Miller, Aubry K.; Brügger, Britta; Kordyukova, Larisa V.; Teleman, Aurelio A. (Nature Communications, 2021)
Abstract - Covalent attachment of C16:0 to proteins (palmitoylation) regulates protein function. Proteins are also S-acylated by other fatty acids including C18:0. Whether protein acylation with different fatty acids has different functional outcomes is not well studied. We show here that C18:0 (stearate) and C18:1 (oleate) compete with C16:0 to S-acylate Cys3 of GNAI proteins. C18:0 becomes desaturated so that C18:0 and C18:1 both cause S-oleoylation of GNAI. Exposure of cells to C16:0 or C18:0 shifts GNAI acylation towards palmitoylation or oleoylation, respectively. Oleoylation causes GNAI proteins to shift out of cell membrane detergent-resistant fractions where they potentiate EGFR signaling. Consequently, exposure of cells to C18:0 reduces recruitment of Gab1 to EGFR and reduces AKT activation. This provides a molecular mechanism for the anti-tumor effects of C18:0, uncovers a mechanistic link how metabolites affect cell signaling, and provides evidence that the identity of the fatty acid acylating a protein can have functional consequences.